Human pulmonary vascular responses to hypoxia and hypercapnia. - Dorrington, K; Talbot, N (2004)
The ability of alveolar gas composition to influence pulmonary vascular tone has been appreciated for over 50 years. In particular, it has been proposed that both O2 and CO2 could play a role in the matching of perfusion to ventilation within the lung, improving the overall efficiency of gas exchange. A wide variety of experimental approaches has been used to investigate pulmonary vascular effects of the respiratory gases in a range of mammalian species. In this article, we review experiments performed in healthy humans, identify particular difficulties in the interpretation of such experiments, and discuss possible approaches to future study.